Two Cases of Primary Testicular Lymphoma Presenting with Direct Spread along the Spermatic Cord and Gonadal Vessels. (18th June 2019) - Ellatif, Mostafa; Kumar, Raekha; Weller, Alexander; Katz, David; Vrentzou, Eirini
Abstract : Primary testicular lymphoma is a rare testicular neoplasm that mainly affects elderly patients, with Human Immunodeficiency Virus (HIV) being a known risk factor in the younger population. Approximately 20% of patients will have disseminated disease with extra-nodal involvement at clinical presentation. Rarely, direct spread along the spermatic cord and gonadal vessels can occur and has been described in the literature. We present two cases of this phenomenon where the primary testicular tumour has spread along the gonadal vein to its origin at the inferior vena cava.